An Analysis of Chemical-Mechanical Damage in Reinforced Concrete Beams - Mohd Noh, Hamidun bin; Sonoda, Yoshimi; Tamai, Hiroki; Kuwahara, Isao (International Journal of Integrated Engineering, 2018)
Nowadays, a major issue in the field of construction is the deterioration of reinforced concrete structures due to chemical and mechanical attacks. This deterioration directly impacts construction safety and serviceability, as well as the cost of maintenance. For the purpose of maintaining safety and serviceability, it is necessary to evaluate the durability of existing structures accurately, in order to predict the structure's deterioration and its future strength. In this study, an experiment was conducted in which the electrolytic process was carried out for several levels of corrosion. Next, a static loading test was adopted to assess the structural performance and obtain the ultimate strength of the beam. In addition, continuum damage mechanics were utilized in the analysis of damage caused by chemical and mechanical effects. Within the framework of this method, chemical damage caused by the corrosion of steel bars was considered. Then the coupling effects of chemical and mechanical damage were calculated by introducing two independent scalar damage variables into the constitutive equation. To calculate the chemical damage evolution, we carried out a diffusion process of chloride ions that impact the corrosion of steel bars in concrete, and an evaluation was conducted on an affected cross-sectional area of a steel bar. The proposed method was found to validate the experiment's results and could predict the ultimate strength under various exposure conditions. Moreover, the proposed orthotropic conditions may be carried out as an alternative to isotropic analysis in order to identify the worst-case scenario of the structure.